Synthesis of urea derivatives via reductive carbon dioxide fixation into contracted porphyrin analogues. Issue 24 (6th November 2017) - Patra, Sajal Kumar; Sahu, Kasturi; Patra, Bratati; Sahoo, Dipak Kumar; Mondal, Sruti; Mukherjee, Payel; Biswal, Himansu S.; Kar, Sanjib
Abstract : Carbon dioxide from ammonium carbonate is trapped by the free base corroles which forms the N 21, N 22 -carbamide-corrole derivatives. Abstract : Carbon dioxide from ammonium carbonate is trapped by the free base corroles with the help of two adjacent inner NH groups ( N 21 and N 22 ) and forms the N 21, N 22 -carbamide-corrole derivatives. There is an extensive literature on functionalized ureas and their potent pharmaceutical applications. While the aliphatic, aromatic, alicyclic, and heterocyclic analogues of differently substituted ureas are well established, the N 21, N 22 -carbamide-porphyrinoid derivatives have been reported rarely. Herein we present a new synthetic protocol to synthesize N 21, N 22 -carbamide-corroles. These results thus open a greener avenue (without using any toxic chemicals like phosgene, CO, or isocyanate) for functionalized urea derivatives bearing porphyrinoid analogues.